Governing the environment salient institutional issues - Breton, Albert; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2009)
This book examines how different countries define and address environmental issues, specifically in relation to intergovernmental relations: the creation of institutions, the assignment of powers, and the success of alternative solutions. It also investigates whether a systemic view of the environment has influenced the policy-making process. The broad perspective adopted includes a detailed analysis of seventeen countries in six continents by scholars from a range of disciplines - economics, political science, environmental science and law - thus producing novel material that moves away from the conventional treatment of decentralisation and the environment in economic literature.
pt. 1. Institutions : alternative solutions to the problem of assigning powers over the environment -- pt. 2. Issues in environmental governance : the comparative advantage of different levels of government.
Includes bibliographical references and index.
Keywords: Environmental policy; Environmental economics; Electronic books